Why did I drop out? Former students' recollections about their study process and factors related to leaving the doctoral studies. Issue 2 (3rd May 2016) - Leijen, Ä.; Lepp, L.; Remmik, M.
ABSTRACT: Recent reforms in higher education have provided material for researching different aspects of doctoral studies in a variety of ways. Much of the current literature concentrates on characteristics of effective supervision and doctoral students' experiences. Less attention has been paid to the study experiences of non-completers – former doctoral students who dropped out of doctoral programmes prior to graduation. In the current study, we explore doctoral studies experiences from the perspective of non-completers and aim to identify factors that were related to dropping out. Data were collected with semi-structured interviews from 14 former doctoral students in the field of education, and qualitative thematic data analysis techniques were employed for data analysis. The results indicate that dropping out from doctoral studies is associated with different factors: for example, (with) students' personal factors, supervisory arrangements, as well as factors related to institution and the wider learning environment. These results are further discussed and implications for enhancing study arrangements for doctoral studies are presented.